2018
DOI: 10.1021/acsanm.8b00338
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Endosomal Escape Using pH-Responsive Nanoparticles with Tunable Disassembly

Abstract: Endosomal escape is a bottleneck in the efficient delivery of therapeutics using nanoparticles; therefore understanding how this property can be optimized is important for achieving better therapeutic outcomes. It has been demonstrated that pH-responsive nanoparticles (pHlexi nanoparticles) have potential to achieve effective escape from the endosomal compartments of the cell. In this paper a library of five pHlexi particles with tunable disassembly pH were synthesized by combining poly(ethylene glycol)-b-poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 32 publications
0
69
0
Order By: Relevance
“…Together, these results strongly demonstrated that both of the lipoplexes could exist in a comparatively stable structure under normal physiological conditions (pH 7.0), while they rapidly release a significant amount of DNA due to the destabilization resulting from the acidic microenvironment in endosomes or lysosomes of tumor cells (pH 5.5) [46,47].…”
Section: Dissociation Kinetics Of Liposome and Dnamentioning
confidence: 64%
“…Together, these results strongly demonstrated that both of the lipoplexes could exist in a comparatively stable structure under normal physiological conditions (pH 7.0), while they rapidly release a significant amount of DNA due to the destabilization resulting from the acidic microenvironment in endosomes or lysosomes of tumor cells (pH 5.5) [46,47].…”
Section: Dissociation Kinetics Of Liposome and Dnamentioning
confidence: 64%
“…Together, these results strongly demonstrated that both of the lipoplexes could exist in a comparatively stable structure under normal physiological conditions (pH 7.0), while they rapidly release a significant amount of DNA due to the destabilization resulting from the acidic microenvironment in endosomes or lysosomes of tumor cells (pH 5.5) [43,44].…”
Section: See Figmentioning
confidence: 64%
“…Together, these results strongly demonstrated that both of the lipoplexes could exist in a comparatively stable structure under normal physiological conditions (pH 7.0), while they rapidly release a signi cant amount of DNA due to the destabilization resulting from the acidic microenvironment in endosomes or lysosomes of tumor cells (pH 5.5) [46,47].…”
Section: Dissociation Kinetics Of Liposome and Dnamentioning
confidence: 66%